Postoperative radiotherapy provides better local control and long‐term outcome in selective cases of cutaneous squamous cell carcinoma with perineural invasion. (12th November 2019) - Cañueto, J.; Jaka, A.; Corchete, L.A.; González‐Pérez, A.Mª.; García‐Castro, R.; Fuente, Mª.J.; Membrive, I.; March, Á.; Mañes, A.; Posada, R.; Pujol, R.M.; Román‐Curto, C.; et al.
Abstract: Background: Perineural invasion (PNI) is a feature of poor prognosis in cutaneous squamous cell carcinoma (CSCC). The benefit of postoperative radiotherapy (PORT) in the management of CSCC with PNI is still not well established. Objectives: We aimed to evaluate the usefulness of PORT in the treatment of CSCC with PNI so as to determine which patients would best benefit from this type of treatment. Methods: A retrospective multicenter cohort of 110 CSCCs with PNI was evaluated. Eighteen recurrent cases were excluded for subsequent analysis. We searched for the types of PNI associated with poor outcome and analysed the effectiveness of PORT on different groups of CSCC with PNI. We also assessed for the usefulness of PORT depending on the surgical margin status (either clear or positive). Results: Postoperative radiotherapy showed clear benefit over observation in CSCC with PNI and positive margins after surgery, where the management by observation increased the risk of poor outcome events 2.43 times ( P = 0.025), and especially in those with positive margins and PNI ≥0.1 mm, where the risk of poor prognosis is eight times greater following a management by observation ( P = 0.0065). Multivariate competing risk analysis preserved statistical significance. Conclusions: The use of PORT on patients with CSCC with PNI and positive margins after surgery, especially in PNI ≥0.1 mm, significantly improves long‐term outcome. The benefit of PORT in cases with clear margins is not as evident, especially in those with PNI of small‐calibre nerves. Clinical trials are imperative.